Integrated cytogenetics and genomics analysis of transposable elements in the Nile tilapia, Oreochromis niloticus - Valente, Guilherme [UNESP]; Kocher, Thomas; Eickbush, Thomas; Simões, Rafael P. [UNESP]; Martins, Cesar [UNESP] (Springer Nature, 2016)
Integration of cytogenetics and genomics has become essential to a better view of architecture and function of genomes. Although the advances on genomic sequencing have contributed to study genes and genomes, the repetitive DNA fraction of the genome is still enigmatic and poorly understood. Among repeated DNAs, transposable elements (TEs) are major components of eukaryotic chromatin and their investigation has been hindered even after the availability of whole sequenced genomes. The cytogenetic mapping of TEs in chromosomes has proved to be of high value to integrate information from the micro level of nucleotide sequence to a cytological view of chromosomes. Different TEs have been cytogenetically mapped in cichlids; however, neither details about their genomic arrangement nor appropriated copy number are well defined by these approaches. The current study integrates TEs distribution in Nile tilapia Oreochromis niloticus genome based on cytogenetic and genomics/bioinformatics approach. The results showed that some elements are not randomly distributed and that some are genomic dependent on each other. Moreover, we found extensive overlap between genomics and cytogenetics data and that tandem duplication may be the major mechanism responsible for the genomic dynamics of TEs here analyzed. This paper provides insights in the genomic organization of TEs under an integrated view based on cytogenetics and genomics.
Keywords: Bioinformatics; DNA mapping; Genomic organization; Repeated DNA